Hubungan Tingkat Pengetahuan Pasien Wanita di Rumah Sakit Haji Adam Malik Medan Tentang Kanker Leher Rahim Dengan Pelaksanaan Deteksi Dini Kanker Leher Rahim - Shafira Utami; Yudha Sudewo; Khairani Sukatendel; Fauzan Azmi Hasti Habibi Samosir; Rizky Adriansyah (Talenta Publisher, 2025)
Introduction.Cervical cancer is a cancer of the lower uterus caused by infection with Human Papilloma Virus (HPV). Various factors in women can influence the incidence of cervical cancer, including sexually transmitted diseases, coitus and separation at young age, multiple partners, parity, and using of oral contraceptive pills. Through prevention measures and early illness identification, the government is attempting to lower the prevalence of cervical cancer. It is important to know the level of knowledge and factors that influence the implementation of early detection because they can affect to carrying out early detection screening. Objectives. To see the relationship between the level of knowledge of married female patients at HAM General Hospital and the implementation of early detection of cervical cancer. Method. The research used an analytic survey study with cross-sectional design will be conducted using questionnaire data with sample of 62 married female patients using a consecutive sampling technique. The analysis using the SPSS program in univariate and bivariate ways with 90% confidence level. Result. From 62 samples, the results obtained were the level of knowledge of respondents in